Evaluation of perioperative complications in patients with obstructive sleep apnea: An observational analysis with clinical implications - Pathlavath Swapna Rathod,; Madhulika Koormala,; Nikhila Choalla,; Indira Priyadarshini CH, (Asian Journal of Medical Sciences, 2024)
Background: Obstructive sleep apnea (OSA) poses significant perioperative risks, yet limited research exists to quantify these complications. Aims and Objectives: The study aims to fill this gap by investigating a variety of perioperative complications in OSA patients. The primary objective was to assess the types and prevalence of perioperative complications across diverse surgical procedures. Materials and Methods: A cohort of 100 OSA patients undergoing different surgical interventions was monitored prospectively. Descriptive statistics, Chi-square tests, independent t-tests, and logistic regression were employed to evaluate the data. Results: In this cohort study involving 100 OSA patients, 57% experienced at least one perioperative complication, most commonly postoperative hypoxemia (23%), cardiac events (18%), and delirium (12%). The mean age for those with complications was 56 years, significantly higher than the 52 years for those without complications (P<0.05). Abdominal surgeries were particularly associated with hypoxemia (P<0.05), while pre-existing cardiac conditions predisposed to cardiac events (P<0.01). Older patients (>60) were more prone to delirium (P<0.05). Complication severity varied, with 29 mild, 20 moderate, and 8 severe cases requiring an intensive care unit. Diabetes and hypertension emerged as significant predictors, with odds ratios of 2.5 and 2.8, respectively (P<0.05). Conclusion: This study highlights the substantial risk of perioperative complications among OSA patients, especially those with certain pre-existing conditions, older age, or undergoing specific types of surgeries. The findings suggest the need for specialized perioperative care plans for these patients to mitigate the risks.